Validated extractive analytical methods for the estimation of pregabalin in bulk and pharmaceutical dosage form - P, PoojaShree.; kumar G P, Senthil; R, Chaithra; D N, Vidya; D R, Bhadresh; S, Manojkumar (International Journal of Advanced Chemistry, 2020)
Two simple, rapid, sensitive and accurate spectrophotometric methods are described for the determination of Pregabalin (PRG) in bulk and pharmaceutical formulations. The methods are based on the reactions of the drug with bromocresol purple (BCP) and bromocresol green (BCG) in buffered hydrochloric acid solutions at pH 1.2 to give coloured ion-pair complexes extractable with chloroform. The coloured products are quantitated spectrophotometrically at 431 nm with BCP and 444.80 nm with BCG. Beer's law is obeyed in the concentration range 10-50 Âµg/ml with both reagents. Recovery studies gave satisfactory results indicating that none of common additives and excipients interfere the assay method. The proposed methods are found to be simple, accurate and reproducible that was successfully applied for the analysis of capsule formulations. The developed methods are easy to use, accurate and highly cost-effective for routine studies relative to HPLC and other techniques.Â Â Â